Urate Oxidase (UOx)-Copper Oxide (CuO)-Carbon Polymer Composite Electrode for Electrochemical Detection of Uric Acid - Buenaventura, Angelo Gabriel E.; Yago, Allan Christopher C. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 32 No 2 (2020), 2020)
This study presents an electrochemical biosensor developed for uric acid (UA) determination using carbon paste electrode (CPE) modified with          copper (II) oxide (CuO) particles and urate oxidase (UOx) enzyme. Base CPE is prepared using a multi-walled carbon nanotube (MWCNT) and a polydimethylsiloxane (PDMS) binder. The main sensing process is based on the oxidation of UA into 5-hydroxyisourate (HIU) as catalyzed by UOx, forming H 2 O 2 as byproduct, and then the H 2 O 2 reduction-oxidation (redox) reaction converts CuO to form Cu 2 O; the amount of H 2 O 2 and hence      UA in the sample is measured by the oxidative current measured for the conversion of Cu 2 O back to CuO. Cyclic Voltammetry (CV) measurements revealed that the activity of UOx was retained with an apparent Michaelis constant (K m app ) to be equal to 41.46 µM. Differential Pulse Voltammetry (DPV) measurements of UA using UOx-CuO-CPE showed a linear response ranging from 10 µM to 79.4 µM UA with a limit of detection (LOD) determined to be equal to 8.82 µM. UOx-CuO-CPE was shown to be selective towards UA even in the presence of creatinine, xanthine, and glucose. Furthermore, UOx-CuO-CPE was shown to be reusable (3.28% RSD), and its fabrication is repeatable using single factor Analysis of Variance (ANOVA) [F(1.396) < F critical (5.143)]. UOx-CuO-CPE was also shown to be stable even after five weeks of storage using the two-sample t-test [t(0.156) < t critical (4.303)]. Based on a recovery test using synthetic urine sample, this study showed the applicability of UOx-CuO-CPE in the detection of UA in human urine with 90.27%–102.03% recovery (n = 3).
Keywords: Urate Oxidase, Copper (II) Oxide, Carbon Paste Electrode, Uric Acid